2020
DOI: 10.1038/s41541-020-0205-6
|View full text |Cite
|
Sign up to set email alerts
|

Review of data and knowledge gaps regarding yellow fever vaccine-induced immunity and duration of protection

Abstract: Yellow fever (YF) virus is a mosquito-borne flavivirus found in Sub-Saharan Africa and tropical South America. The virus causes YF, a viral hemorrhagic fever, which can be prevented by a live-attenuated vaccine, strain 17D. Despite the vaccine being very successful at decreasing disease risk, YF is considered a re-emerging disease due to the increased numbers of cases in the last 30 years. Until 2014, the vaccine was recommended to be administered with boosters every 10 years, but in 2014 the World Health Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 57 publications
0
56
0
1
Order By: Relevance
“…An open question remains, however, regarding the length of immunity conferred by SARS-CoV-2 vaccines. For those infectious diseases that are contained by neutralizing antibodies, peak titers have been shown to predict durability (43)(44)(45). As such, SpFN may offer longer protection than counterparts; though this requires empirical confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…An open question remains, however, regarding the length of immunity conferred by SARS-CoV-2 vaccines. For those infectious diseases that are contained by neutralizing antibodies, peak titers have been shown to predict durability (43)(44)(45). As such, SpFN may offer longer protection than counterparts; though this requires empirical confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,51 Importantly, several studies concluded that nAb titers also decline over time after vaccination. 54,61,77,[79][80][81][82] These observations, added to the aforementioned observation that primary vaccination induces less seroconversion in individuals from endemic regions, support that endemic regions may profit more from booster vaccinations as compared to non-endemic areas, 18,83 as discussed further below.…”
Section: Immune Responses To Yf-17d Booster Vaccinationmentioning
confidence: 67%
“…However, as vaccination does not always confer immunity against a disease for a small number of people and for certain durations, the assumption of immunity from yellow fever vaccination must continue to be considered. In 2014, the World Health Assembly adopted the recommendation to remove the 10-year booster dose requirement from the IHR (Staples et al, 2020). Evidence had shown that a single primary dose of the yellow fever vaccine was sufficient to confer sustained immunity and lifelong protection, however since then this recommendation and the durability of protective immunity has been questioned (ibid.…”
Section: Vaccine Developmentmentioning
confidence: 99%